2013
DOI: 10.12984/eed.31373
|View full text |Cite
|
Sign up to set email alerts
|

Ortaokul Öğrencilerinin Teknolojiye Yönelik Tutumlarının Bazı Değişkenler Açısından İncelenmesi

Abstract: Bu çalışmanın amacı ortaokul öğrencilerinin teknolojiye yönelik tutumlarının bazı değişkenler açısından incelenmesidir. Çalışmada, genel tarama modeli kullanılmıştır. Araştırmanın örneklemini Kars il merkezindeki ve merkeze bağlı köylerdeki altı orta okulda öğrenim gören ve random olarak seçilen 6., 7. ve 8. sınıftaki toplam 400 ortaokul öğrencisi oluşturmaktadır. Çalışmada teknolojiye yönelik tutum ölçeğinin Türkçe versiyonu (ÖTYT-TR) kullanılmıştır. Öğrencilerin teknolojiye yönelik tutumlarında cinsiyet ve y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…However, the studies of Çakır (2012) and Güzeller (2011) on PISA samples revealed significant differences in favour of male students" attitudes towards computers. Similarly, the studies of Altun (2011), Üzel and Özdemir (2008), Gürbüzoğlu-Yalmancı and Aydın (2014 with primary school students and Tekindal, Ertekin and Tekindal (2010) with high school students gave similar results. Moreover, the study of Çelik and Ceylan (2009) brought about significant differences in favour of female students.…”
Section: Discussion Results and Suggestionsmentioning
confidence: 55%
“…However, the studies of Çakır (2012) and Güzeller (2011) on PISA samples revealed significant differences in favour of male students" attitudes towards computers. Similarly, the studies of Altun (2011), Üzel and Özdemir (2008), Gürbüzoğlu-Yalmancı and Aydın (2014 with primary school students and Tekindal, Ertekin and Tekindal (2010) with high school students gave similar results. Moreover, the study of Çelik and Ceylan (2009) brought about significant differences in favour of female students.…”
Section: Discussion Results and Suggestionsmentioning
confidence: 55%
“…The reason for this result may be that men generally have a more positive view of technology than cats. Many studies have concluded that men's attitudes towards technology are more positive than women [11][12][13].…”
Section: Resultsmentioning
confidence: 99%